1989
DOI: 10.1177/002199838902300901
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Analysis of a Postbuckled Embedded Delamination

Abstract: Delamination growth caused by local buckling of a delaminated group of plies was investigated. Delamination growth was assumed to be governed by the strain-energy release rates GI, GII, and GIII. The strain-energy release rates were calculated using a geometrically nonlinear, three-dimensional, finite element analysis. The program is described and several checks of the analysis are discussed. Based on a limited parametric study, the following conclusions were reached:1. The problem is definitely mixed-mode. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(58 citation statements)
references
References 11 publications
0
58
0
Order By: Relevance
“…Almost all of the papers on delamination buckling deal with beams and flat plates [3][4][5][6][7][8][9][10]. The early work belongs to Chai et al [11] who characterized the delamination buckling models by the delamination thickness and the number of delaminations through the laminate thickness.…”
mentioning
confidence: 99%
“…Almost all of the papers on delamination buckling deal with beams and flat plates [3][4][5][6][7][8][9][10]. The early work belongs to Chai et al [11] who characterized the delamination buckling models by the delamination thickness and the number of delaminations through the laminate thickness.…”
mentioning
confidence: 99%
“…The crack closure method was used to calculate the strain energy release rate at the delamination front. Comparison of their results with the existing three-dimensional result [12] indicated that their method was sufficient and accurate.…”
Section: Introductionmentioning
confidence: 91%
“…The phenomenon of progressive failure in laminated composite structures is yet to be understood, and as a result, reliable strategies for designing optimal laminated composite structures for desired life and strength are not yet available [1] For the past two decades analytical and numerical analysis have been carried out by many researchers [2][3][4][5][6][7][8][9][10][11][12][13][14] to analyse delaminated composite structures, considering their buckling and post-buckling behaviour. The early work belongs to Chai et al [2] who characterized the delamination buckling models by the delamination thickness and number of delaminations through the laminate thickness.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of VCCT formulae for different element types was given by Krueger (2004). Whitcomb (1989) was one of the first to introduce the use of the VCCT to determine Strain Energy Release rate distributions for a circular delamination. Since then, a lot of numerical analyses have been performed by using this technique: many of them dealing with delamination growth initiation (Mukherjee et al, 1994)- (Whitcomb,1992), others with growth evolution (Klug et al, 1996) When dealing with three-dimensional problems, the one-step Virtual Crack Closure Technique (VCCT) is generally used instead of the two-steps Virtual Crack Closure Technique in order to reduce the computational time requested for the analysis.…”
Section: Delamination Growth Criteriamentioning
confidence: 99%